From Academic Pressure to Preventive Self-Help: Development of Academic Burnout Mitigation Guide for Students - Moh. Alwi Hasan; Permata Sari; Moh. Alwi Hasan; Permata Sari; Tuti Wantu (Universitas Negeri Malang, 2026)
Academic burnout has become a significant concern in higher education due to increasing academic demands and its impact on students’ well-being and performance. Despite the availability of counseling services, structured self-help resources specifically designed to mitigate academic burnout remain limited. This study aimed to develop and examine the content validity and acceptability of an Academic Burnout Mitigation Guide designed as a self-help resource for university students. The research employed a Research and Development (R&D) approach adapted from the Borg and Gall model up to the operational product revision stage. The validation process involved nine experts representing guidance and counseling, design and media, and Indonesian language, as well as 11 prospective student users. Data were collected using acceptability scales covering appropriateness, usefulness, attractiveness, and ease of use, and analyzed using Aiken’s V index alongside qualitative feedback. The results indicated a very high level of content validity and acceptability, with an Aiken’s V index of 0.87 from experts and 0.85 from prospective users. These findings suggest that the guide demonstrates strong conceptual alignment and operational feasibility as a preventive self-help tool. The study concludes that the validated guide provides a theoretically grounded and practically acceptable foundation for subsequent effectiveness testing in broader higher education contexts.